UJI AKTIVITAS SITOTOKSIK EKSTRAK KULIT BATANG KAYU MANIS (Cinnamomum burmannii) TERHADAP KULTUR SEL T47D - Wiwin Herdwiani; Endang Sri Rejeki (Jurnal Farmasi Indonesia, 2015)
Cinnamon is plant commonly used as an aroma enhancer in cooking. Cinnamon can be used as an alternative cancer treatment. The content of cinnamon bark essential oil including, safrole, cinnamaldehyde, eugenol, tannins, flavonoids, saponins. This study aimed to examine the cytotoxic activity of ethanol extract skin cinnamon to inhibit T47D breast cancer cell activity. Ethanol extract skin cinnamon was obtained through maceration method by 96% ethanol. The content of flavonoids and cinnamaldehyde was detected by Thin Layer Chromatography (TLC). Cytotoxic test on breast cancer cells T47D used 3-[4,5-dimetilthiazol-2yl]-2,5-difeniltetrazolium bromide (MTT) method and the absorbance was read at ELISA reader. Parameter single cytotoxic test is IC50.and its cytotoxic activity was compared with doxorubicin. The result showed that ethanol extract skin cinnamon had cytotoxic effect on breast cancer T47D with IC50 71,157 Î¼g/ml. The ethanol extract skin cinnamon has the potential to be developed as a cemoprefentive agency.